Low-Temperature Sintered Pb(Zr,Ti)O-3-Pb(Mn,Sb)O-3-Pb(Zn,Nb)O-3 for Multilayer Ceramic Actuators - Wan, Dandan; Li, Qian; Choi, Joo-Young; Choi, Ji-Won; Yang, Ying; Yoon, Seok-Jin (IOP PUBLISHING LTD, 2010)
A quaternary 0.90Pb(Zr0.48Ti0.52)O-3-0.05Pb(Mn1/3Sb2/3)O-3-0.05Pb(Zn1/3Nb2/3)O-3 (0.90PZT-0.05PMS-0.05PZN) piezoelectric ceramic was synthesized by a conventional method, and CuO was adopted to lower its sintering temperature. The crystal structure, micromorphology, and electrical properties were studied in terms of CuO content. The results indicate that 1.0 wt% CuO addition significantly improves the sinterability of 0.90PZT-0.05PMS-0.05PZN ceramics, lowering the sintering temperature to 900 degrees C and maintaining moderate electrical properties: d(33) = 306 pC/N, Q(m) = 997, k(p) = 53.6%, tan delta = 0.50%, and epsilon(T)(33)/epsilon(0) = 1350. The low-temperature sintering behavior could be explained by the formation of a transient liquid phase by CuO during sintering. Moreover, the endothermic peak at about 950 degrees C in the differential thermal analysis (DTA) curve of the raw ceramic powder provides further evidence of an amorphous phase. To obtain better piezoelectric properties, La2O3 was selected as the donor dopant for the 0.90PZT-0.05PMS-0.05PZN + 1.0 wt% CuO system. Our study demonstrates that La2O3 is very effective in improving piezoelectric properties, markedly increasing d(33) and k(p) without decreasing Q(m). Finally, 0.5 wt% La2O3 added 0.90PZT-0.05PMS-0.05PZN + 1.0 wt% CuO ceramics show excellent electrical properties: d(33) = 355 pC/N, Q(m) = 936, k(p) = 58.4%, tan delta = 0.32%, and epsilon(T)(33)/epsilon(0) = 1590, which are quite suitable for multilayer piezoelectric ceramic actuators. (C) 2010 The Japan Society of Applied Physics
Keywords: POWER PIEZOELECTRIC PROPERTIES; MORPHOTROPIC-PHASE-BOUNDARY; SUBSTITUENTS; TRANSFORMER; ZNO